2021
DOI: 10.46909/journalalse-2021-002
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physicochemical Characterisation of Date Palm Cultivars From Ghardaïa (Southeast Algeria)

Abstract: The date palm (Phoenix dactylifera L.) is an economically important species vital for food security in Algeria, especially for the southern population. There are an estimated 18 million palm trees in Algeria with more than 1000 cultivars. This poorly known resource is unfortunately threatened with extinction. This work was carried out on 24 date palm cultivars, studying their morphological and physicochemical characteristics, such as the weight, length and diameter of the date and the seed, and the consistency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(1 reference statement)
0
2
1
Order By: Relevance
“…result of this study pinnae number, pinnae width and length, and trunk height traits were showed significant values at p ≤ 0.05 whereas Boudeffeur et al, (2021) reported that these traits showed nonsignificant value at p ≤ 0.05. Additionally, Khalilia et al, (2022) and Allam et al (2021) also reported the fruits width showed significant variation between date palm cultivars while this trait revealed contrary result in this study.…”
Section: Discussioncontrasting
confidence: 51%
“…result of this study pinnae number, pinnae width and length, and trunk height traits were showed significant values at p ≤ 0.05 whereas Boudeffeur et al, (2021) reported that these traits showed nonsignificant value at p ≤ 0.05. Additionally, Khalilia et al, (2022) and Allam et al (2021) also reported the fruits width showed significant variation between date palm cultivars while this trait revealed contrary result in this study.…”
Section: Discussioncontrasting
confidence: 51%
“…Principal component analysis performed on the fruits and seeds of 24 different cultivars from Southeastern Algeria showed large variability between cultivars. 10 of the 14 traits examined were found to be strong discriminating factors (Allam et al, 2021).…”
Section: Group and Study Of Correlations Between Cultivars: Principal...mentioning
confidence: 91%
“…The soils are sandy to sandy-silty. The salinity rate is very high with values between 1.37g/l and 1.43g/l (Allam et al, 2021). Our experimental site is characterized by a soil sandy-silt, with 70 % fine sand.…”
Section: Experimental Site and Planting The Materialsmentioning
confidence: 97%